(untitled) (American Journal of Islam and Society, 2006)
This paper offers a critical assessment of the Chinese Communist Party’s post-9/11 efforts to build international support for its security activities in its Xinjiang province. Xinjiang has traditionally presented the party with a particular challenge. It is remote and relatively underdeveloped, has borders with seven countries, and, most importantly, is inhabited by a large, concentrated, and restive Islamic minority known as the Uygurs. The party is very concerned about the presence of separatist elements among the Uygur population. Beijing’s activities to control such elements have traditionally been quite secretive. However, after 9/11, a Beijing-released report claimed that Xinjiang’s separatist activity is Islamist in nature and that groups operating within the region have ties to al-Qaeda and the Taliban. I argue that inconsistencies surrounding this report tend to undermine the party’s position. Furthermore, given the nature of Islamic practice in Xinjiang and the historical development of Uygur-Han relations in the region, it is more likely that the primary motivations for separatism are rooted in ethno-nationalist, rather than religious, considerations.